Electroless Ni–B sealing on nanoporous anodic aluminum oxide pattern: deposition and evaluation of its characteristic properties - Muralidharan Sundararajan; Mutharasu Devarajan; Mariatti Jaafar (Journal of Materials Research and Technology, 2022)
Suitable coatings on electronic packaging substrates are generally preferred to surround the internal components, protect them from adverse conditions, and improve heat-dissipating performance. Such coatings are developed using different deposition techniques to attain a cosmetic appearance on a single sheet, preferably aluminium alloys. These coatings have to overcome certain challenges, including heat dissipation and mechanical robustness. In this study, a nickel–boron (NiB) binary alloy was sealed and deposited on an already developed nanoporous anodic aluminium oxide (AAO) pattern using an electroless deposition method. The performance is studied with respect to different deposition times. The resulting NiB layer has a nano nodular-like morphology with a 0.95-μm layer thickness. The structural analysis shows a mixture of amorphous and crystalline nature with sharp Ni peaks (111), (220), including the crystallite size of 377 nm. Compared with the bare Al substrate, the 1-hr NiB sealing on AAO has a significant reduction in thermal resistance (Rth) to 29.65%, a rise in junction temperature (Tj) to 27.36%, and improved bulk thermal conductivity (k) to 50.1%. In addition, this binary NiB exhibits a roughness of 0.89 μm, an indentation hardness of 2560 MPa, and a scratch hardness of 8764 MPa. Results show enhanced properties of the AAO sealed binary NiB coating as a feasible option for packaging substrates.